1991
DOI: 10.1037/0021-843x.100.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Social phobia: Axis I and II correlates.

Abstract: The presence of Axis I and Axis II disorders in 71 social phobic patients was examined. Generalized anxiety disorder was the most common secondary Axis I disorder, followed by simple phobia. Avoidant personality disorder and obsessive-compulsive personality disorder were the most common Axis II diagnoses, and 88% of the sample exhibited features of these 2 personality styles. Subjects with additional Axis I diagnoses were more anxious and depressed than those with no additional Axis I disorder. Social phobics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 12 publications
1
51
0
2
Order By: Relevance
“…4 Peter et al concluded that socially anxious adolescents are more likely to form online friendships and prefer to communicate with strangers online rather than face to face. 16 Indeed, the Internet has been found to assist people who are isolated or disabled in developing social relationships.…”
Section: Hypothesis 4: Interpersonal Relationships Will Have a Negatimentioning
confidence: 98%
See 1 more Smart Citation
“…4 Peter et al concluded that socially anxious adolescents are more likely to form online friendships and prefer to communicate with strangers online rather than face to face. 16 Indeed, the Internet has been found to assist people who are isolated or disabled in developing social relationships.…”
Section: Hypothesis 4: Interpersonal Relationships Will Have a Negatimentioning
confidence: 98%
“…1,2 Other studies have explored whether the cyber-relationship substitutes for an unmet need in an actual relationship. [3][4][5] Together, these studies indicate that cyber-relationships can provide a sense of belonging, warmth, and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…O segundo transtorno observado com maior freqüência foi o transtorno de personalidade paranóide, que ocorreu em 27% da amostra. À primeira vista o resultado parece surpreendente, pois sua ocorrência foi menor em outros estudos (Turner et al, 1991;Alnaes e Torgersen, 1988;Jansen et al, 1994;Sanderson et al, 1994). Entretanto, Grant et al (2005), em seu estudo cuja amostra era composta de mais de 40 mil sujeitos, diagnosticaram o transtorno de personalidade paranóide em 29% dos fóbicos sociais, um resultado idêntico ao deste estudo.…”
Section: Discussionunclassified
“…Isto parece ocorrer por haver sobreposição de critérios diagnósticos entre ambos (Turner et al, 1991;Schneier et al, 1991;Widiger e Shea, 1991;Marteinsdottir et al, 2001;Tilfors et al, 2004). Para alguns destes autores (Turner et al, 1991;Schneier et al, 1991;Widiger e Shea, 1991), fobia social de subtipo generalizado e transtorno de personalidade esquiva descrevem a mesma condição psicopatológica. Em outros estudos, transtornos de personalidade, que não o transtorno de personalidade esquiva, também foram observados, porém, com menor freqüência.…”
Section: Introductionunclassified
“…In studies of comorbidity between AVPD and social phobia prior to DSM-IV, considerable overlap was found (Alnaes & Torgersen, 1988;Brooks, Baltazar, & Munjack, 1989;Fahlen, 1995;Heimberg, Hope, Dodge, & Becker, 1990;Jansen, Arntz, Merckelbach, & Mersch, 1994;Sanderson, Wetzler, Beck, & Betz, 1994;Turner, Beidel, Borden, Stanley, & Jacob, 1991). Earlier studies that have compared patients with the generalized social phobia with and without AVPD argued for quantitative, not qualitative, differences between the two groups (Boone et al, 1999).…”
Section: Avpd and Social Phobiamentioning
confidence: 99%